Phenomenology and clinical course of movement disorder in GNAO1 variants: Results from an analytical review. (April 2019) - Schirinzi, Tommaso; Garone, Giacomo; Travaglini, Lorena; Vasco, Gessica; Galosi, Serena; Rios, Loreto; Castiglioni, Claudia; Barassi, Claudia; Battaglia, Domenica; Gambardella, Maria Luigia; Cantonetti, Laura; Graziola, Federica; et al.
Abstract: GNAO1 variants were recently discovered as causes of epileptic encephalopathies and heterogeneous syndromes presenting with movement disorders (MDs), whose phenomenology and clinical course are yet undefined. We herein focused on GNAO1 -related MD, providing an analytical review of existing data to outline the main MD phenomenology and management, clinical evolution and genotype-phenotype correlations. Reviewing 41 previously published patients and assessing 5 novel cases, a comprehensive cohort of 46 patients was analyzed, reassuming knowledge about genotypes, phenotypes, disease course and treatment of this condition. GNAO1 -related MD consisted of a severe early-onset hyperkinetic syndrome, with prominent chorea, dystonia and orofacial dyskinesia. Symptoms are poorly responsive to medical therapy and fluctuate, with critical and life-threatening exacerbations, such as status dystonicus. The presence of a choreiform MD appears to be predictive of a higher risk of movement disorder emergency. Surgical treatments are sometimes effective, although severe disabilities persist. Differently from the early infantile epileptic encephalopathy phenotype (associated with loss of function variants), no clear correlation between genotype and MD phenotype emerged, although some variants recurred more frequently, mainly affecting exons 6 and 7. Highlights: A comprehensive review of MD features in GNAO1 -encephalopathy is provided. Movement disorder is a core feature of GNAO1 -encephalopathy. Choreiform movement disorder is a risk factor for movement disorder emergencies. Variants affecting the Arg 209 residue cause a prominent movement disorder phenotype. Loss of function variants cause more frequently early onset epileptic encephalopathy.